PENINGKATAN HASIL BELAJAR OPERASI HITUNG BILANGAN BULAT MENGGUNAKAN ALAT PERAGA PAPAN JODOH BILPOTIF, DAN CD WARNA: SMP NEGERI 2 PAKEM BONDOWOSO - TIEN ROOSTINI (Mitra Pendidikan, 2022)
This research was carried out based on the following problems: those that emerged during the learning of integer arithmetic operations in class VII students of SMP Negeri 2 Pakem in the 2019/2020 school year. The purpose of this study was to improve student learning outcomes and motivation in integer arithmetic operations. This research is an action research with two rounds. The target of this research is class VIIA students. The data obtained in the form of formative test results, achieving completeness of 88%, the results of observation of learning activities of 90% of active students. The conclusion of this research is that the teaching aids on the bilpotif board have a positive effect on learning outcomes and are very motivating for seventh grade students in learning integer arithmetic operations.